Constipation‐associated factors in outpatients with schizophrenia: A multicenter questionnaire survey - Taro Tazaki; Hiroki Yamada; Ryotaro Sato; Hiroki Ishii; Shutaro Sugita; Haruka Yanagihara; Dan Nakamura; Osamu Takashio; Atsuko Inamoto; Akira Iwanami (Wiley, 2024)
Abstract Constipation is a prevalent gastrointestinal disorder that affects people globally, decreasing their quality of life and life expectancy. Individuals with schizophrenia often suffer from constipation, which could be a result of the illness itself or the side effects of psychotropic medications. However, little research has been conducted on factors contributing to constipation in individuals with schizophrenia. To address this issue, we conducted a survey using self‐administered questionnaires and medical records to identify factors associated with constipation in psychiatric outpatients. This study included 399 patients with schizophrenia, resulting in a high prevalence of constipation (43.4%). The analysis suggested that female gender, the doses of antiparkinsonian medications, and benzodiazepine sleeping pills may be associated with constipation.